PENYULUHAN PENGGUNAAN APLIKASI ABSS ACCOUNTING DI SMA NEGERI 3 PADANG - Sanda Patrisia Komalasari; Dika Amelia Agustina; Silmi Silmi; Fitriyeni Oktavia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This article aims to provide information about community service activities carried out by Accounting Students at Andalas University. Service activities carried out in the form of counseling on the ABSS Accounting Application. Counseling was carried out to students of SMA Negeri 3 Padang class XI IPS. The ABSS Accounting application is a computer-based accounting application. Counseling aims to provide understanding and skills to participants in using the ABSS Accounting application. In this counseling, participants were introduced to various basic concepts of ABSS Accounting and their use. At the end of the counseling, questionnaires were distributed to students to see their opinions regarding the counseling being carried out. The results show that this activity brings positive value to the students. This activity is useful and motivates them so it needs to be continued.